Biologically active carbazole derivatives: focus on oxazinocarbazoles and related compounds. (2nd April 2014) - Bouaziz, Zouhair; Issa, Samar; Gentili, Jacques; Gratz, Andreas; Bollacke, Andre; Kassack, Matthias; Jose, Joachim; Herfindal, Lars; Gausdal, Gro; Døskeland, Stein Ove; Mullié, Catherine; Sonnet, Pascal; et al.
Abstract: Four series of carbazole derivatives, including N-substituted-hydroxycarbazoles, oxazinocarbazoles, isoxazolocarbazolequinones, and pyridocarbazolequinones, were studied using diverse biological test methods such as a CE-based assay for CK2 activity measurement, a cytotoxicity assay with IPC-81 cell line, determination of MIC of carbazole derivatives as antibacterial agents, a Plasmodium falciparum susceptibility assay, and an ABCG2 -mediated mitoxantrone assay. Two oxazinocarbazolesIb andIg showed CK2 inhibition with IC50  = 8.7 and 14.0 µM, respectively. Further chemical syntheses were realized and the 7-isopropyl oxazinocarbazole derivative2 displayed a stronger activity against CK2 (IC50  = 1.40 µM). OxazinocarbazolesIb, Ig, and2 were then tested against IPC-81 leukemia cells and showed the ability to induce leukemia cell death with IC50 values between 57 and 62 μM. Further investigations were also reported on antibacterial and antiplasmodial activities. No significant inhibitory activity on ABCG2 efflux pump was detected.